The influence of long distance running on sonographic joint and tendon pathology: results from a prospective study with marathon runners. Issue 1 (December 2016) - Proft, Fabian; Grunke, Mathias; Reindl, Christiane; Mueller, Felix; Kriegmair, Maximilian; Leipe, Jan; Weinert, Peter; Schulze-Koops, Hendrik; Witt, Matthias
Abstract Background The impact of physical exercise on joints and tendons is still a matter of debate. The aim of this study was to investigate with ultrasound the acute effects of extreme physical exercise on knee and ankle joints and their surrounding structures in trained athletes. Methods Participants of the Munich marathon were examined by arthrosonography before and after long distance running. Ultrasound assessment included grey scale and power Doppler examination of the knee and talocrural joints with surrounding tendons. Findings consistent with joint effusion, tendon and/or entheseal pathologies were documented. In addition to the ultrasound evaluation, information on training habits and past or present arthralgia or joint swelling was gathered. Results One Hundred Five runners completed both the pre- and post-excercise ultrasound assessments (baseline and follow-up), resulting in the sonographic evaluation of 420 knee and talocrural joints. At baseline, 105 knee (50) and 38 talocrural joints (18.1) showed effusions, compared to 100 knee (47.6) and 33 talocrural joints (15.7 %) at follow-up. The differences were not significant (p > 0.05 each). Effusion size did not correlate with the timepoint of ultrasound assessment and was independent of covariates such as gender, age or running distance. Hypervascularity of the patellar tendon was detected in 21 cases (10.0 %) at follow-up in contrast to one at baseline (p < 0.001). This observation was more frequent in male than in female participants (p < 0.05). Conclusions Acute physical stress is significantly associated with hypervascularity of the patellar tendon. No significant changes of synovial effusion were detected in knee and talocrural joints.